Narrative Technique in Salman Rushdie’s Midnight’s Children (TUTA Journal, 2022)
This research paper is whole-heartedly focused on the narrative technique of Salman Rushdie’s Midnight’s Children, one of his major novels. The study is supposed to be very significant simply because it exposes post modern narrative technique that Rushdie exploits in it. The research method exploited in this research paper are numerous, but at the same time it gives focus on  magic realism, admixture of fantasy and reality.  Rushdie, in Midnight’s Children, uses political allegory during the narration and he exposes Saleem as an allegorical figure., who is made to move through time with an ease for his narration. One can notice it when he calls himself as having “a metaphorical” relation to the nation. Rushdie’s narrative technique which fills the readers with wonder makes them believe what his narrator says. Similarly, through its first person and fallible narrator, Rushdie’s novel falls within the category of metafiction. Rushdie has presented how post modern writers build meaning on the use of old and new forms along with genres, such as allusions, other inter texts, kitsch, fabricated or invented quotations from other literary and non-literary texts. After reading the novel, it enables the reader to comprehend how Rushdie has made impact on the Indian English writers with his innovative way of writing novel.